Anesthetic Efficacy of a Combination of 4% Prilocaine/2% Lidocaine with Epinephrine for the Inferior Alveolar Nerve Block: A Prospective, Randomized, Double-blind Study - Cook, Olivia; Nusstein, John; Drum, Melissa; Fowler, Sara; Reader, Al; Draper, John (Journal of endodontics, 2018)
Prilocaine plain has a high pH and concentration (4%), which could decrease the pain of injection and increase success. The purpose of this study was to compare pain associated with anesthetic solution deposition and the degree of pulpal anesthesia obtained with the combination of prilocaine and lidocaine versus a lidocaine and lidocaine combination when used for inferior alveolar nerve blocks (IANBs). One hundred eighteen asymptomatic subjects were randomly given a combination of 1 cartridge of 4% prilocaine plain plus 1 cartridge of 2% lidocaine with 1:100,000 epinephrine or a combination of 2 cartridges of 2% lidocaine with 1:100,000 epinephrine for the IANB at 2 separate appointments. Subjects rated the pain associated with anesthetic solution deposition of injection. Mandibular teeth were tested with an electric pulp tester every 4 minutes for 57 minutes. Anesthesia was considered successful when 2 consecutive 80 readings were obtained within 17 minutes and the 80 reading was continuously sustained for 57 minutes. Comparisons for anesthetic success were analyzed using the exact McNemar test, and pain ratings associated with anesthetic solution deposition were analyzed using multiple Wilcoxon matched pairs signed rank tests; both were adjusted using the step-down Bonferroni method of Holm. Four percent prilocaine plain was significantly less painful upon anesthetic solution deposition. Pulpal anesthetic success was not significantly different between the 2 combinations. The combination of 4% prilocaine plain plus 2% lidocaine with 1:100,000 epinephrine did not increase pulpal anesthetic success for IANBs compared with a combination of 2 cartridges of 2% lidocaine with 1:100,000 epinephrine. Pain associated with anesthetic solution deposition from the first cartridge of 4% prilocaine plain was significantly less when compared with the first cartridge of 2% lidocaine with 1:100,000 epinephrine.